What Have Macroeconomists Learned about Business Cycles from the Study of Seasonal Cycles? - Miron, Jeffrey A.; Beaulieu, J. Joseph (The Review of Economics and Statistics, 1996)
Jeffrey A. Miron, J. Joseph Beaulieu, What Have Macroeconomists Learned about Business Cycles from the Study of Seasonal Cycles?, The Review of Economics and Statistics, Vol. 78, No. 1 (Feb., 1996), pp. 54-66